1990
DOI: 10.1007/bf00023158
|View full text |Cite
|
Sign up to set email alerts
|

Variation between genotypes of carnation (Dianthus caryophyllus cultivars and interspecific hybrids) in time of flowering and response to long days. I. Variation in yield distribution

Abstract: Early flowering carnation cultivars, responding to artificial long days, can assist the grower to plan the onset of flowering and achieve a better distribution of flower production over the year . A comparative trial is described of 20 carnation genotypes (cultivars and backcrosses of interspecific hybrids), representing a wide variation in flowering time and response to long days . The trial was planted in September in a phytotron under a winter light intensity of 15 W/mz for eight hours per day . In one half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although we primarily selected 8 lines with a longer response time among the progeny of the crosses between ethyleneresistant lines (Table 2), we were not able to select lines with an extremely long vase life despite a replicated test in the second year (data not shown). Another problem is that the progeny of this cross tend to show late flowering (in other words, tend to delay flower bud differen- tiation), which is generally unsuitable for practical cultivation compared with early-flowering cultivars of carnation (Sparnaaij et al, 1990). Therefore, we finally concluded that crosses between ethylene-resistant lines were ineffective to produce lines with both ethylene resistance and an extremely long vase life.…”
Section: Discussionmentioning
confidence: 93%
“…Although we primarily selected 8 lines with a longer response time among the progeny of the crosses between ethyleneresistant lines (Table 2), we were not able to select lines with an extremely long vase life despite a replicated test in the second year (data not shown). Another problem is that the progeny of this cross tend to show late flowering (in other words, tend to delay flower bud differen- tiation), which is generally unsuitable for practical cultivation compared with early-flowering cultivars of carnation (Sparnaaij et al, 1990). Therefore, we finally concluded that crosses between ethylene-resistant lines were ineffective to produce lines with both ethylene resistance and an extremely long vase life.…”
Section: Discussionmentioning
confidence: 93%
“…In Part I of this paper (Sparnaaij et al ., 1990), genetic variation in average flowering date and response to a mid-winter LD treatment (dusk to dawn lighting) was studied in a phytotron experiment comparing a wide range of genotypes, partly derived from interspecific breeding programs . That study revealed a considerable potential for early flowering and a strong response to LD in several types of interspecific hybrids .…”
Section: Introductionmentioning
confidence: 99%